2019
DOI: 10.1155/2019/4102646
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Based Catalyst from Pyrolysis of Waste Tire for Catalytic Ethanol Dehydration to Ethylene and Diethyl Ether

Abstract: This work investigated the use of waste tire as a source of carbon in preparation of carbon-based catalysts for applying in ethanol dehydration. The pyrolysis of waste tire was performed to obtain the solid carbon, and then it was treated with two different acids including HCl and HNO3 prior to the activation process with different temperatures to gain suitable carbon catalysts. All carbon catalysts were characterized using nitrogen physisorption, XRD, FTIR, and acid-base titration. The catalysts were tested f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“…It has been demonstrated that 30P/BC-AC(BA) has excellent catalytic performance. The performances of 30P/BC-AC(BA) and different catalysts using H 3 PO 4 modification [31][32][33], different carbon-based catalysts [7,9,19,34], and other catalysts [35], with respect to ethanol conversion, ethylene selectivity, and DEE selectivity were compared as shown in Table 6. It has been demonstrated that 30P/BC-AC(BA) has excellent catalytic performance.…”
Section: Stability Testmentioning
confidence: 99%
“…It has been demonstrated that 30P/BC-AC(BA) has excellent catalytic performance. The performances of 30P/BC-AC(BA) and different catalysts using H 3 PO 4 modification [31][32][33], different carbon-based catalysts [7,9,19,34], and other catalysts [35], with respect to ethanol conversion, ethylene selectivity, and DEE selectivity were compared as shown in Table 6. It has been demonstrated that 30P/BC-AC(BA) has excellent catalytic performance.…”
Section: Stability Testmentioning
confidence: 99%
“…As reaction temperature increased and time progressed, the peak at 1.76 min increased, particularly with the hydrothermal GAC catalysts and Amberlyst-15. Sulfonated and phosphorylated carbons can catalytically dehydrate ethanol forming diethyl ether and ethylene, suggesting these compounds as possible byproducts . The increase in 2-HIBA conversion with the GAC-HT-18M and Amberlyst-15 on increasing the temperature from 120 to 150 °C (1 h of residence time), and with the GAC-HT-2M on increasing the residence time to 3 h at 150 °C did not affect the ester yield, yet led to an increase in the formation of byproducts.…”
Section: Resultsmentioning
confidence: 93%
“…Sulfonated and phosphorylated carbons can catalytically dehydrate ethanol forming diethyl ether and ethylene, suggesting these compounds as possible byproducts. 47 The increase in 2-HIBA conversion with the GAC-HT-18M and Amberlyst-15 on increasing the temperature from 120 to 150 °C (1 h of residence time), and with the GAC-HT-2M on increasing the residence time to 3 h at 150 °C did not affect the ester yield, yet led to an increase in the formation of byproducts. We therefore concluded that reaction temperatures of 120 °C for the GAC-HT-18M and Amberlyst-15, and 150 °C for the GAC-HT-2M at 1 h of residence time were optimal for 2-HIBA esterification.…”
Section: Reaction Studiesmentioning
confidence: 95%
“…4 In 2016, around 17 million tons of tires were manufactured globally, which leads to a vast quantity of waste tires production annually. 5 Eventually, it will create waste tire disposal issues and a negative impact on the environment because waste tires are not easy to decompose and could remain for up to 100 years in the environment. Moreover, traditional disposal methods, such as incineration and landfill, could result in pollutant emissions and land occupation.…”
mentioning
confidence: 99%